Are multiple-choice items unfair? And if so, for whom?. (December 2019) - Siegfried, Christin; Wuttke, Eveline
Due to their test economy and objective evaluability, multiple-choice items are used much more frequently to test knowledge than constructed-response questions. However, studies point out that dependencies may exist between the individual test result and the test format (multiple-choice or constructed-response). Studies testing economic knowledge (one dimension of economic competence) are using mainly multiple-choice items and indicate gender-specific performance in the corresponding tests in favour of male test-takers. As an explanation for these "gender differences" gender-specific affinities and differences in cognitive abilities are mentioned. Moreover, the test format itself is mentioned but has hardly been investigated in detail to date. In order to answer the question to what extent students test performance depends on the item format, we test economic knowledge using two test formats (constructed-response and multiple-choice), but with the same content. Results from 201 business and business education students show that the usage of constructed-response items can compensate for existing gender differences in 53% of all cases. This underlines that no general, gender-specific advantage or disadvantage can be assumed in relation to the item format. However, the mixed use of constructed-response and multiple-choice items seem promising to compensate for potential gender differences.